PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK PADA PEMBELAJARAN IPAS MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI KELAS IV SDN 02 NGADIWARNO - Khusnul Khotimah Wulandari; Ferina Agustini; Choirul Huda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the limitations of media and monotonous learning methods in the applied learning process, especially in science learning. The purpose of this research is to develop pop up book learning media in science learning on the topic "Plants as Sources of Life on Earth" for grade IV of SDN 02 Ngadiwarno. The development of this pop up media uses the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. This media is designed to improve understanding through a visual- kinesthetic approach, strengthen memory with dual coding techniques, and foster student motivation and learning independence. The validity of the media was tested by media experts and material experts, with the results of media expert I obtaining a percentage of 100% with the category "Very Valid", media expert II obtaining a percentage of 95.5% with the category "Very Valid", material expert I obtaining a percentage of 100% with the category "Very Valid", and material expert II obtaining a percentage of 94.2% with the category "Very Valid". Then, the teacher response assessment obtained a percentage of 95.5% with the category "Appropriate" and the student response assessment obtained a percentage of 94.5% with the category "Appropriate". So the development of pop-up book learning media in the science learning material "Plants as Sources of Life on Earth" meets the criteria and is suitable for use in the learning process in class IV SDN 02 Ngadiwarno.